Endocuticle is involved in caste differentiation of the lower termite. Issue 5 (30th January 2021) - Ye, Chenxu; Song, Zhuanzhuan; Wu, Taoyu; Zhang, Wenxiu; Saba, Noor us; Xing, Lianxi; Su, Xiaohong
Abstract: Caste differentiation in termites is one of the most conspicuous examples of facultative polyphenism in animals. It is clear that specific cuticular formation occurs in hard exocuticles during caste differentiation. However, the developmental pattern of the soft endocuticle in the differentiation pathways of castes is unknown. To reveal whether the endocuticle is involved in caste differentiation, we compared the exocuticle and endocuticle thickness of individuals in 2 pathways (nymph line and worker line) of caste differentiation in the termite Reticulitermes aculabialis . The endocuticle protein genes were identified by transcriptome analysis and the expression patterns of these genes were confirmed in caste differentiation. We found that the endocuticle structure showed dynamic changes in 2 pathways, and the first difference in endocuticle structure occurred after larvae differentiation bifurcated into workers and nymphs. The thinning of the endocuticle was a significant event from nymphs developing into alates with the thickest exocuticle and thinnest endocuticle. The thickest endocuticle layers were found in the heads of the workers and the ultrastructure of the endocuticle in the heads was more complex than that in the thorax–abdomens. Six endocuticle protein genes were identified and annotated as endocuticle structural glycoproteins SgAbd-2, SgAbd-9, and Abd-5. The expression levels of endocuticle protein genes changed dramatically during caste development and the expression levels in neotenic reproductives (secondary reproductives) were significantly higher than those in alates (primary reproductives). These results reveal the roles of endocuticles in caste differentiation and adaptation to the environment.